2021
DOI: 10.18502/ijph.v50i4.5997
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Psychological Intervention on Negative Emotion, Cancer-Related Fatigue and Level of Hope in Lung Cancer Chemotherapy Patients Based on the PERMA Framework

Abstract: Background: Psychological status is a decisive factor for regulating the lung cancer chemotherapy patients’ levels of fatigue and hope. Using the PERMA (Positive Emotion, Engagement, Relationships, Meaning, and Accomplishment) framework. We aimed to explore the influences of the psychological intervention on the patients’ negative emotion, cancer-related fatigue, and level of hope. Method: A total of 100 lung cancer chemotherapy patients admitted in Wuhan No.4 Hospital, China, from Jan 2018 to Aug 2019 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 14 publications
1
44
0
Order By: Relevance
“…Chemotherapy can inhibit the growth of cancer cells but may result in collateral damage to adjacent normal cells, which elicits multiple complications after treatment [ 2 ]. It has been reported that lung cancer patients after chemotherapy are prone to adverse psychological states such as depression, anxiety, fatigue, and irritability [ 3 , 4 ]. Moreover, lax treatment compliance may cause disease recurrence [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy can inhibit the growth of cancer cells but may result in collateral damage to adjacent normal cells, which elicits multiple complications after treatment [ 2 ]. It has been reported that lung cancer patients after chemotherapy are prone to adverse psychological states such as depression, anxiety, fatigue, and irritability [ 3 , 4 ]. Moreover, lax treatment compliance may cause disease recurrence [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Music therapy is a systematic interventional process in which the therapist utilizes various forms of musical experience, and the therapeutic relationship is developed during the course of therapy as a therapeutic motivator to help the treated person achieve healthy goals. Today, the PERMA model-based nursing concept has been gradually popularized in clinical practice, and excellent results have been achieved in the treatment of lung cancer, posttraumatic stress disorder, and other diseases [ 10 , 11 ]. But its application effect in AHF is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…18 The Positive emotions, Engagement, Relationships, Meaning and Accomplishment model (PERMA) may represent a meaningful framework for positive psychology interventions to enhance positivity and hope. [19][20][21] We interpret the association found between emotional function and finding an agreeable activity related to the concept of "optimal experience or flow." When people do activities that they love, they are completely in the present moment, oblivious to anything else.…”
Section: Emotionsmentioning
confidence: 63%
“…22 In the flow state, the attention shifts to the task at hand, allowing symptoms and limitations to fade. 21 Another key component associated with emotions revealed in this analysis is nurturing (active effort) supportive relationships. Our results confirm and extend the previous report about the need to address the quality of relationships and caregiving to improve difficult emotions (anxiety/depression).…”
Section: Emotionsmentioning
confidence: 88%